Knowledge of Undergraduate Nursing Students about Palliative Care - Fitriani Fitriani; Rizka Wahyuni; Al Ikhsan Agus (NHM PRESS, 2023)
This study aimed to find out the level of knowledge of nursing students about palliative care. This study was a quantitative descriptive research with a cross-sectional approach. The sampling technique utilized purposive sampling technique with the total sample of 287 participants, consisting of 133 undergraduate nursing students from Universitas Sam Ratulangi and 154 undergraduate nursing students from Universitas Muslim Indonesia. The instrument employed to measure the knowledge level of undergraduate nursing students toward palliative care was the Palliative Care Quiz for Nurses-Indonesian Version (PCQN-I). The majority of undergraduate nursing students' knowledge level was categorized less, with 198 (69%) students and 89 (31%) students had sufficient knowledge level regarding palliative care. The average percentage of respondents' correct answers on philosophy and principles of palliative care aspect, psychosocial and spiritual care aspect, as well as pain and symptom management aspect were 29.1%, 11,03%, and 34.89%, respectively. The level of knowledge of undergraduate nursing students towards palliative care is categorized less, especially in psychosocial and spiritual care aspect.